2015
DOI: 10.1038/jp.2015.127
|View full text |Cite
|
Sign up to set email alerts
|

Primary palliative care in the delivery room: patients’ and medical personnel’s perspectives

Abstract: Caregiver's emotional distress primarily originates from providing support to parents and not from providing medical care to the dying newborn. Implications for future practice include the need for structured education to improve DR staff's communication and counselling skills related to parents in PPC situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The route should be painless and easy to handle to facilitate parental proximity. An umbilical9 16 catheter was used in most of our cases, much more frequently than in other studies; a single patient had a peripheral catheter and some had less invasive routes. Little is known about the efficacy of minimally invasive routes; one study has suggested that intranasal fentanyl limits laboured breathing in dying neonates 26…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The route should be painless and easy to handle to facilitate parental proximity. An umbilical9 16 catheter was used in most of our cases, much more frequently than in other studies; a single patient had a peripheral catheter and some had less invasive routes. Little is known about the efficacy of minimally invasive routes; one study has suggested that intranasal fentanyl limits laboured breathing in dying neonates 26…”
Section: Discussionmentioning
confidence: 91%
“…This proportion is high for DR comfort care, compared with other studies, but fairly low compared with NICU deaths. Four studies of DR comfort care have mentioned medication use 16. A study of four  units (two in the USA, one in Canada and one in the Netherlands) reported 23 extremely preterm newborns who died with DR comfort care: none received comfort medication;17 a French unit reported that 3 of 19 babies received medication 9.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations